Characteristics of microplastic pollution and analysis of colonized-microbiota in a freshwater aquaculture system. (1st August 2022) - Li, Weixin; Chen, Xiaofeng; Cai, Zeming; Li, Minqian; Liu, Zhihao; Gong, Han; Yan, Muting
Abstract: The microbial communities associated with microplastics (MPs) and their ambient environments have received wide attention. Although previous studies have reported the differences of microbial communities between MPs and natural environment or substrates, the effects of MPs on microbial balance and functions in ambient water remain unclear, particularly for aquaculture water. Here, we investigated the MPs pollution in farm ponds of grass carp located in the Foshan City of Guangdong Province and reported the distinction of bacterial structures, functions, and complexity between microbiota on MPs and in water. MPs with an average abundance of 288.53 ± 74.27 items/L in pond water were mostly fibers and cellulose, mainly transparent and in size of 0.5–1 mm. Structures and functions of bacterial communities on MPs significantly differed from that in pond water. A large number of enriched or depleted OTUs on MPs compared with water belong to the phylum Proteobacteria, the predominant phylum in microbial communities on MPs and in water. Some species included in the phylum Proteobacteria have been shown to be cellulose-degrading and pathogenic. Microbiota on MPs exhibited higher species richness and diversity as well as a more complex network than that in water, illustrating MPs as a distinct habitat in the aquaculture system. Graphical abstract: Image 1 Highlights: Microplastics were abundant in grass carp ponds in Foshan City. Significantly different bacterial structures and functions were on MPs compared to water. Distinct OTUs between MPs and water mainly belong to the phylum Proteobacteria. MPs microbiota had higher species richness and diversity and a more complex network compared to microbiota in water. MPs can be a distinct habitat in the aquaculture system.